IMMUNE CELLS MEDIATED EFFECTS OF SODIUM CHLORIDE ON THE DEVELOPMENT OF VASCULAR INFLAMMATION AND ABDOMINAL AORTIC ANEURYSM IN ANGIOTENSIN II-TREATED APOE-KO MICE. (April 2021) - Stegbauer, Johannes; Yakoub, Mina; Rahman, Masudur; Hering, Lydia; Potthoff, Sebastian; Argov, Doron; Flögel, Ulrich; Rump, Lars Christian; Temme, Sebastian
Abstract : Objective: Chronic high salt (NaCl) intake is a major risk factor for cardiovascular diseases. Recent studies showed that excessive chronic NaCl intake affects immune response and thereby contributes to the pathogenesis of vascular injury. However, it remains unclear whether NaCl intake initially primes immune cell response by promoting memory T cells and sensitize the development of vascular injury in response to a subsequent stimulus. Design and method: Therefore, we investigate whether 14 days of NaCl treatment (1% NaCl) followed by a 7 day washout period affects the incidence and outcome of abdominal aortic aneurysms (AAA) in apolipoprotein E deficient (ApoE-KO) mice infused chronically with angiotensinII (AngII) (1000ng/kg/min) via osmotic minipumps for 10 days. Assessment of AAA was done by magnetic resonance imaging (MRI). To visualize vascular inflammation in vivo, perfluorocarbon nano-emulsions (PFC) injected intravenously before and 2, 4, 7 and 10 days after chronic AngII infusion were detected by combining 1H/19F MRI using a 19F RARE sequence. After 10 days of AngII infusion, aortas with perivascular fat were dissected. Aortic inflammation and immune cells infiltration were analyzed by flow cytometery, immunohistology and realtime PCR. Results: The survival rate of ApoE-KO mice pretreated with NaCl was significantly lower and the AAA incidence rate was significantly higher compared to sham-treated apoE-KO mice. The amount of 19F signal detected in areas of AAA was significantly increased in apoE-KO mice pretreated with NaCl. Histological analysis confirmed these results and showed that most of the immune cells were in the PVAT rather than dwelling in the vascular tissues. At day 10, proinflammatory cytokines like TNF-alpha, iNOS and TGF-ß as well as numbers of neutrophils, monocytes, effector memory CD4 and CD8 T cells were significantly higher in aortas of NaCl pretreated apoE-KO mice compared to sham-treated mice. Moreover, NaCl augmented the development of effector Th1 CD4 and effector CD8 cells from naïve T cells in vitro, respectively. Conclusions: In conclusion, these results suggest a significant role of NaCl in priming immune cell phenotype and thereby mediating vascular inflammation and damage in AngII infused apoE-KO mice.